PP.22.23: SYSTOLIC BLOOD PRESSURE. KEY ELEMENT OF PREDICTION OF THE DEATH RISK IN PATIENTS WITH ACUTE CARDIAC FAILURE. (June 2015) - Axente, L.; Chioncel, V.; Ionescu, I.; Sinescu, C.
Abstract : Objective: Systolic blood pressure (SBP) measured at hospital admission is an important prognostic factor in predicting the risk of death during hospitalization and at 3 months after discharge in patients with preserved left ventricular function and in those with systolic dysfunction. Design and method: We conducted a prospective study on a sample of 101 patients hospitalized from January 2005 to April 2008, with the diagnosis of heart failure; they were followed up until 30.06.2010. The studied variables were: demographic data, data about heart failure etiology, comorbidity, smoker status, clinical factors (SBP, pulse rate, NYHA class at admission, systemic or pulmonary congestion, atrial fibrillation, BMI), echocardiographic data, electrocardiograms, laboratory and therapeutic factors. Results: The probability of survival over t = five years for a person with heart failure, selected by chance from the studied population, is S (t = 5 years) = 0, 4231. It should be noted that 49.8% of patients survive more than 44 months. Note that 50, 32% of the men with heart failure survive more than 42 months and 50% of the female patients survive more than 48 months. It is also confirmed for patients with acute heart failure included in the study that even a slight increase in ejection fraction can improve the prognosis. The intensity of the risk falls with 4.6% with every increasing unit of the ejection fraction. SBP measured at admission is a key element in predicting the risk of death during hospitalization and after discharge, in patients with preserved left ventricular function and those with systolic dysfunction. The intensity of the risk decreases with 2, 03% for every increasing unit (1 mmHg) of SBP. Conclusions: 1. Systolic blood pressure measured at hospital admission is a key element in predicting the risk of death during hospitalization, and in patients with acute heart failure. 2. The prognostic value of this parameter is maintained 5 years after hospital discharge, mortality being directly proportional with the decrease of systolic blood pressure, regardless of the therapy followed. 3. The prognostic value of this marker is just as important as the ejection fraction of the left ventricle.